A Flexible Extension of the Drosophila Ultrabithorax Homeodomain Defines a Novel Hox/PBC Interaction Mode. - Foos, N.; Maurel-Zaffran, C.; Maté, M.J.; Vincentelli, R.; Hainaut, M.; Berenger, H.; Pradel, J.; Saurin, A.J.; Ortiz-Lombardía, M.; Graba, Y. (Structure, 2015)
The patterning function of Hox proteins relies on assembling protein complexes with PBC proteins, which often involves a protein motif found in most Hox proteins, the so-called Hexapeptide (HX). Hox/PBC complexes likely gained functional diversity by acquiring additional modes of interaction. Here, we structurally characterize the first HX alternative interaction mode based on the paralogue-specific UbdA motif and further functionally validate structure-based predictions. The UbdA motif folds as a flexible extension of the homeodomain recognition helix and defines Hox/PBC contacts that occur, compared with those mediated by the HX motif, on the opposing side of the DNA double helix. This provides a new molecular facet to Hox/PBC complex assembly and suggests possible mechanisms for the diversification of Hox protein function.